Perlindungan Hukum Terhadap Anggota dalam Arisan Online - Muharawati; Ismail Ali; Fitrah; Elvira; Surahman (YP-SDI Lamaddukelleng, 2025)
This study aims to determine the legal status of the parties involved in online arisan (social savings and credit) and the legal protection provided to them. This study uses normative legal research techniques, focusing on document review in library research. Based on the research results, it can be concluded that this study discusses the legal status of the parties involved in online arisan and the forms of legal protection provided. Owners, administrators, and participants are bound by a contractual relationship based on Article 1320 of the Civil Code. Legal protection is provided preventively through written agreements and electronic evidence, and repressively through lawsuits for breach of contract or fraud in accordance with the Civil Code and the ITE Law.